Metacognitive Reading Strategies of EFL Learners: A Narrative Research - Armin Fani; Nia Karuniasih; Ika Rusdiati (TEFLA Journal (Teaching English as Foreign Language and Applied Linguistics Journal), 2021)
EFL learner need abundant knowledge of metacognitive reading strategies to improve their reading comprehension process. Since, the employment of metacognitive reading strategies has positive correlation with reading comprehension achievement. Thus, it is a worth conducting to investigate the metacognitive reading strategies employment by EFL learner. This study aims to investigate (1) what are metacognitive strategies employed by EFL learners in before-reading, during-reading, and after-reading phases? (2) how do EFL learners employ their metacognitive reading strategies? Conducting through narrative principle, the result of this study shows that particular metacognitive reading strategies were employed by the participant of this research. The result also show that the strategies were employed based on problem and purpose of reading comprehension process. Therefore, effective reading comprehension process should be equipped with reading comprehension employment.